1′S-1′-Acetoxyeugenol acetate: A new chemotherapeutic natural compound against MCF-7 human breast cancer cells - Nagoor, Noor Hasima; In, Lionel Lian Aun; Azmi, Mohamad Nurul; Aziz, Ahmad Nazif; Thirthagiri, Eswary; Ibrahim, Halijah; Awang, Khalijah (Elsevier, 2010)
Medicinal plants containing active natural compounds have been used as an alternative treatment for cancer patients in many parts of the world especially in Asia (Itharat et al. 2004). In this report, we describe the cytotoxic and apoptotic properties of 1′S-1′-acetoxyeugenol acetate (AEA), an analogue of 1′S-1′-acetoxychavicol acetate (ACA), isolated from the Malaysian ethno-medicinal plant Alpinia conchigera Griff (Zingiberaceae) on human breast cancer cells. Data from MTT cell viability assays indicated that AEA induced both time- and dose-dependant cytotoxicity with an IC50 value of 14.0 μM within 36 h of treatment on MCF-7 cells, but not in HMEC normal control cells. Both annexin V-FITC/PI flow cytometric analysis and DNA fragmentation assays confirmed that AEA induced cell death via apoptosis. AEA was also found to induce cell cycle arrest in MCF-7 cells at the G0/G1 phase with no adverse cell cycle arrest effects on HMEC normal control cells. It was concluded that AEA isolated from the Malaysian tropical ginger represents a potential chemotherapeutic agent against human breast cancer cells with higher cytotoxicity potency than its analogue, ACA.